Social Media and Digital Breakage on the Sports Beat - Lowes, Mark and Robillard, Christopher (International Journal of Sport Communication, 2018)
This scholarly commentary draws on existing sport communication literature in an exploration of social media’s role in, and impact on, sport journalism practices and the production of sport news. Of particular concern is the emergence of a form of citizen sport journalism that usurps the traditional role of sport journalists as gatekeepers of the relationship between the sports world and its multitude of audiences. It is argued that social media are providing audiences with more opportunities to create the type of mediated discourses they want to experience by eliminating the scarcity of time and space that once privileged the gatekeeping status of sport journalists. Consequently, sport reporters are becoming social-media content creators and curators while competing against spectator sport-news content creators. Whereas these changes might have a negative connotation, the authors conclude that sport coverage in digital culture offers more opportunities for journalists to step outside the confines of traditional sport journalism work routines and news-production practices.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEyMy9panNjLjIwMTgtMDA4OA